Evaluasi Implementasi Program Rekrutmen, Seleksi dan Penempatan Pegawai Blud Puskesmas di Kabupaten Lampung Tengah - Ali Subagiyo; Fatqul Hajar Aswad; M. Badrun; Siswoyo Siswoyo (Universitas Malahayati Lampung, 2026)
ABSTRACT The Recruitment, Selection, and Placement Program for Public Health Center BLUD Personnel in Central Lampung district has been implemented since 2023 until now, so it is appropriate to evaluate the series of processes that have occurred. This study aims to determine: (1) the results of the context evaluation; (2) the results of the input evaluation; (3) the results of the process evaluation; (4) the results of the product evaluation of the Recruitment, Selection, and Placement Program for Public Health Center BLUD Personnel in Central Lampung district in 2024. This research uses a qualitative approach with a descriptive method. The evaluation model used is the context, input, process, product (CIPP) model. The four aspects in the CIPP model, namely context, input, process, and product, help the decision-making process to answer four basic questions regarding: (1) what should be done; (2) how to implement it; (3) whether it was carried out according to plan; (4) whether the implemented program was successful. The results of the research on the Recruitment, Selection, and Placement Program for Public Health Center BLUD Personnel in Central Lampung district indicate that based on the context evaluation, the activities are carried out based on regulations, the existence of needs and objectives for fulfilling human resource needs. Based on the input evaluation, there are fulfillment of prospective employee requirements, selection stages according to provisions, the existence of a selection committee, the availability of selection funding, and the preparation of facilities and infrastructure is quite good. Based on the process evaluation, there are efforts to disseminate information on prospective employee recruitment, there are prospective employee applicants, there is an administrative selection, a written selection is carried out, there is an interview test, and the time provided is sufficient. Based on the product evaluation, it was found that the formation is fulfilled, the quality of new personnel is as expected, the level of acceptance of work culture is good, new personnel can adapt and work effectively, there is a decrease in the workload of old personnel, there is an increase in service quality, the performance of new personnel is in accordance with expectations, new personnel have good work commitment and motivation. Keywords: Evaluation, Implementation, Recruitment, Public Health Center. ABSTRAK Program Rekrutmen, Seleksi dan Penempatan Tenaga BLUD Puskesmas di Kabupaten Lampung Tengah telah dilaksanakan sejak tahun 2023 hingga sekarang, sehingga sudah layak dievaluasi serangkaian proses yang telah terjadi. Penelitian ini bertujuan untuk mengetahui : (1) hasil evaluasi konteks (context); (2) hasil evaluasi masukan (input); (3) hasil evaluasi proses (process); (4) hasil evaluasi produk (product) Program Rekrutmen, Seleksi dan Penempatan Tenaga BLUD Puskesmas di Kabupaten Lampung Tengah tahun 2024. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Model evaluasi yang digunakan adalah model context, input, process, product (CIPP). Empat aspek dalam model CIPP yaitu context, input, process, dan product membantu proses pengambil keputusan untuk menjawab 4 (empat) pertanyaan dasar mengenai : (1) apa yang harus dilakukan; (2) bagaimana melaksanakannya; (3) apakah dikerjakan sesuai rencana; (4) apakah program yang dilaksanakan berhasil. Hasil penelitian Program Rekrutmen, Seleksi dan Penempatan Tenaga BLUD Puskesmas di Kabupaten Lampung Tengah menunjukkan bahwa berdasarkan evaluasi konteks (context), kegiatan dilaksanakan berpedoman pada regulasi, adanya kebutuhan dan tujuan pemenuhan kebutuhan SDM. Berdasarkan evaluasi masukan (input) terdapat pemenuhan syarat calon pegawai, tahapan seleksi sesuai ketentuan, adanya panitia seleksi, tersedianya pembiayaan seleksi, dan penyiapan sarana dan prasarana cukup baik. Berdasarkan evaluasi proses (process) terdapat upaya penyebaran informasi penerimaan calon pegawai, adanya pendaftar calon pegawai, adanya seleksi administrasi, dilakukan seleksi tertulis, adanya pelaksanaan tes wawancara, dan waktu yang disediakan cukup. Berdasarkan evaluasi produk (product) ditemukan keterpenuhan formasi, kualitas pegawai baru sesuai harapan, tingkat penerimaan budaya kerja baik, pegawai baru dapat beradaptasi dan bekerja efektif, terjadi penurunan beban kerja pegawai lama, adanya peningkatan mutu layanan, kinerja pegawai baru sesuai dengan harapan, pegawai baru memiliki komitmen dan motivasi kerja yang baik. Kata Kunci: Evaluasi, Implementasi, Rekrutmen, Puskesmas.